A comparative study of spoken word poetry and its literary counter-part - Zakaria, Haidy Tarek (AUC Knowledge Fountain, 2019)
This thesis discusses the contrast between spoken word and literary poetry, bearing in mind the differences in imagery, allusions and performance methods. Though both are fall under the same genre, the differences between them show as they are compared. There are many similarities between the two and the differences are not clear cut, however, upon closer inspection, one finds that the use of metaphor, and similes differ from one form to another. The fact that spoken word poetry uses performance as part of the poem also casts a difference between the two forms.